2015
DOI: 10.1051/fruits/2015003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pure oxygen and reduced oxygen modified atmosphere packaging on the quality and microbial characteristics of fresh-cut pineapple

Abstract: -Introduction. Modified atmosphere packaging (MAP) is a preservation technique currently used by the fresh-cut fruit industry. Fruit quality may vary according to the concentration of oxygen (O 2 ) in the packaging. However, there is no published research on the effects of a pure O 2 modified atmosphere in the packaging of fresh-cut pineapple. There are also no comparative studies of the differences between pure O 2 and conventional low O 2 MAP on the quality of fresh-cut pineapple. Materials and methods. Pine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
9
0
5
Order By: Relevance
“…Previous studies have reported the potential effect of low O 2 atmosphere and cold storage to retard microbial growth of fresh or minimally processed fruit. For instance, Pan et al . observed low O 2 (4 kPa) and enriched CO 2 (5 kPa) markedly reduced the growth of yeast and mould on fresh‐cut pineapple at 10 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the potential effect of low O 2 atmosphere and cold storage to retard microbial growth of fresh or minimally processed fruit. For instance, Pan et al . observed low O 2 (4 kPa) and enriched CO 2 (5 kPa) markedly reduced the growth of yeast and mould on fresh‐cut pineapple at 10 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the potential effect of low O 2 atmosphere and cold storage to retard microbial growth of fresh or minimally processed fruit. For instance, Pan et al 40 observed low O 2 (4 kPa) and enriched CO 2 (5 kPa) markedly reduced the growth of yeast and mould on fresh-cut pineapple at 10 ∘ C. For pomegranate arils of cv. Wonderful stored under low O 2 (5 kPa), a higher aerobic mesophilic bacteria count was reported at 5 ∘ C in comparison with this current study.…”
Section: Microbial Growthmentioning
confidence: 99%
“…It is well known the effect of MAP with high CO 2 and low O 2 on reducing softening during postharvest storage of fruits and vegetables, which has been attributed to the reduction of either the activity of cell‐wall‐degrading enzymes or the metabolic activity of the product . For example, the application of 4 kPa O 2 + 5 kPa CO 2 delayed the loss of firmness in fresh‐cut pineapple, and similar atmospheric conditions positively influenced firmness in fresh‐cut apples compared to air conditions . In this work, the application of active MAP only helped to retain firmness of uncoated samples, whereas coated samples were not benefited by MAP.…”
Section: Resultsmentioning
confidence: 67%
“…However, they have also been described negative effects. Thus for example, the application of 4 kPa O 2 + 5 kPa CO 2 delayed firmness loss in fresh-cut pineapple (Pan et al, 2015) and similar atmospheric conditions positively influenced firmness in fresh-cut apples compared to air conditions . However, high CO 2 levels caused softening and electrolyte leakage in cut peppers (López-Gálvez et al, 1997) and low O 2 and high CO 2 (10-20 kPa) MAPs did not prevent softening of fresh-cut pears , bananas or apples .…”
Section: Prevention Of Texture Loss In Fresh-cut 'Rojo Brillante' Permentioning
confidence: 92%
“…It is well known the effect of MAP with high CO 2 and low O 2 on reducing softening during postharvest storage of fruits and vegetables, which has been attributed to the reduction of either the activity of cell-wall-degrading enzymes or the metabolic activity of the product (Toivonen and Hampson al., 2009). For example, the application of 4 kPa O 2 + 5 kPa CO 2 delayed firmness loss in fresh-cut pineapple (Pan et al, 2015), and similar atmospheric conditions positively influenced firmness in fresh-cut apples compared to air conditions . In this work, the application of active MAP only helped to retain firmness of uncoated samples, whereas coated samples were not benefited by MAP.…”
Section: Colour and Polyphenol Oxidase (Ppo) Activity Of Fresh-cutmentioning
confidence: 98%